SAT0568 Rheumatological manifestations in a series of patients with chikungunya fever. (15th June 2017) - Duran, AM Sapag; Beron, AM; Duran, S Sapag; Cristado, C Coral; Medina, G; Nasswetter, G; Dubinsky, D
Abstract : Background: Chikungunya fever is characterised by a high probability of persistent rheumatological manifestations, producing a negative impact in the work, social and economic fields. Objectives: To determine the frequency and type of rheumatologic involvement in the subacute and chronic phase of Chikungunya fever. Methods: Descriptive, cross-sectional study. We included patients>16 years old with Chikungunya infection (real time PCR, IgM or IgG for Chikungunya) who consulted consecutively for rheumatic symptoms/signs from March 2015 to March 2016. According to the time of evolution, the disease was divided in 2 Phases: acute (≤10 days of duration) and subacute/chronic (≥11 days). According to clinical presentation, patients were classified in two groups: 1) non-autoimmune rheumatologic compromise (NARC) and 2) autoimmune rheumatologic compromise (ARC). Current ACR/EULAR criteria for classification of autoimmune diseases were used. Results: Two hundred and two patients were evaluated, 80 were excluded due to negative serology for Chikungunya. 122 were included: 107 (88%) female, mean age 52.52±13.19 years, and time of evolution of 116.66±91.61 days. Acute phase. 122 patients: fever 85 (69.67%), rash and pruritus 54 (44.26%), tenosynovitis 23 (18.8%), polyarthralgias 100 (82%) and arthritis 56 (45.90%). Chronic phase . 122 patients: 71 (58%) patients had a chronic persistent rheumatologic symptoms and 51 (42%) presented remission of symptoms but all of them presented subsequent recurrence in an 91±40 days. NARC in 33 patients (27%) and ARC in 89 (73%), with no significant differences in age and time of evolution was observed. NARC: 14 (42.4%) exacerbation of previous osteoarthritis pain, 9 (27.3%) developed fibromyalgia and 10 (30.3%) had localized soft tissue pain. ARC: 13 (14.6%) with a history of RA, SLE, psoriasis or DM reactivated the underlying disease and 76 (85.4%) developed ARC: Undifferentiated polyarthritis with negative antibodies 61 (80%), RA with positive antibodies 5 (6.5%), scleroderma 2 (2.6%), cutaneous vasculitis 2 (2.6%), polymyalgia rheumatica 1 (1.3%), Sjogren's Syndrome 2 (2.6%), Dermatomyositis 1, Erythema nodosum 1 (1.3%) and vitiligo 1 (1.3%). Antibodies were requested according to clinical suspicion: FAN ≥320 in 5 patients, RF in 6, ACPA in 4 and anti RO in 1. Thyroid dysfunction was observed in 7 patients who had a previous normal thyroid profile. Conclusions: The frequency of rheumatological manifestations post Chikungunya fever in our sample was high, and can trigger ARC. Patients presenting new immunological manifestations in an endemic area for Chikungunya fever should have a serologic test performed. This series of patients must be evaluated with long-term studies to define their evolution, under the possibility of developing definite autoimmune disease or remission. References: Chikungunya Pathology and Cytokines. Chow et al. JID 2011 . Disclosure of Interest: None declared